ANALYSIS FLOOD AND HYDRAULICS IN SUB KENDALSARI - KEDAWUNG MALANG CITY - Ilham Nurilfiansyah; Winda Harsanti (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
Flood and hydraulic analysis aims to evaluate the hydraulic conditions and flood potential of the Kendalsari–Kedawung drainage channel in Malang City. This area is densely populated, characterized by high rainfall intensity and rapid land development, which increases surface runoff volume. Therefore, a FLOOD AND HYDRAULIC ANALYSIS OF THE KENDALSARI–KEDAWUNG DRAINAGE CHANNEL IN MALANG CITY is required. The methods applied in this study include hydrological analysis using the Rational Method, which produced a channel capacity of Q = 0.505 m³/s. To determine the design discharge and hydraulic simulation using EPA SWMM software to assess the capacity of the existing channel. The objective of this analysis is to evaluate the current channel condition, and the results indicate that Channel K is unable to accommodate the peak discharge, leading to flood risk. After redesigning Channel K by adjusting the channel elevation, the surface runoff volume can be effectively controlled, and channel overflow is eliminated. For the redesign cost calculation of the drainage system at Point K, the required budget is IDR 458,283,905.